Akuntabilitas Implementasi Kebijakan Pesantren Ramah Anak : Evaluasi Model CIPP Di Pesantren Putri Al Mawaddah - Hanif Musthofa Al Fajri; Mami Hajaroh (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to describe the accountability of implementing the Child-Friendly Islamic Boarding School (PRA) policy at Al Mawaddah Coper Ponorogo Girls' Islamic Boarding School. It examines accountability across context, input, process, and product aspects, focusing on transparency, responsibility, and evaluation. The research employs a mixed-methods approach with a concurrent embedded design using the CIPP evaluation model. Data were collected through interviews, questionnaires, observation, and documentation, involving school leaders, administrators, teachers, musrifah, and santriwati. Quantitative data were analyzed using descriptive statistics, while qualitative data followed the Miles and Huberman interactive model. The findings indicate that context accountability reached 76% (accountable), input accountability 73.5% (accountable), process accountability 69% (moderately accountable), and product accountability 71.75% (accountable). The results show that although the policy has been implemented relatively well, challenges remain in monitoring, evaluation, and stakeholder participation. Therefore, this study recommends strengthening monitoring and evaluation systems, improving human resource capacity, and refining internal regulations to enhance the sustainability and effectiveness of the PRA policy implementation.